Aspergillus spp. and azole-resistance characterization on filtering respiratory protective devices from waste sorting industry - Viegas, Carla (2020)
Studies performed on the waste management industry have reported Aspergillus as the most frequent genera on waste-sorting, incineration and composting. Filtering respiratory protective devices (FRPD) are disposable after one-day use (workshift) and their use is mandatory in Portuguese wastesorting industries. During FRPD use, humidity and temperature conditions provide a favorable environment for Aspergillus growth retained. The aim of this study was to characterize Aspergillus spp. presence in FRPD interior layer and exhalation valves, as well as to detect possible azole-resistant isolates in this complex indoor environment.